PERU BAHAN MORFOLOGI RUMAH TINGGAL 01 KAMPUNG ARAB KOTA MALANG (The Morphological Changes of the Residential Houses of Kampong Arab at Malang City) - Aryati, Allafa; Antariksa, Antariksa; Wardhani, Dian Kusuma (Unika Soegijapranata Semarang, 2012)
Kampong Arab at Malang City represents an urban kampong that was built within the influence of the Dutch Govemments policy (Regering Regleement and Vremde Oosterllngen). Therefore, the kampong has colonial, Javanese, and Islamic styles in its architectural constructions. However, the modernization of the region brought changes in its visual appearance; many old buildings were replaced by modem ones. The objectives of this study were to identify the history and the characteristics ofthe old buildings at Kampong Arab by applying descriptive method (field observation and secondary data), to identify and analyze the changes of the old buildings by using evaluative description method (scoring method), and to identify and analyze the factors that cause changes to the old buildings by using evaluative description method (factor analysis). The results of the study show that 4 buildings underwent big changes, 27 buildings got moderate changes, and 11 buildings had only little changes. The causes of the changes of the old buildings are grouped into three, namely (1) factors of ownership and location, (2) factors of age and maintenance, and (3) factors that is related to social, cultural and family size affairs.